Handbook of research on SDGs for economic development, social development, and environmental protection - Popescu, Cristina Raluca Gh., 1983- (Advances in industrial ecology (AIE) book series, 2022)
"This book provides an updated view of the newest trends, novel practices and latest tendencies concerning the manner of supporting and ensuring sustainability and the challenges of Post-COVID-19 Era, while focusing on economic development, social development, and environmental protection"--